Prodromus of a fern flora for Bolivia. X. Hymenophyllaceae - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2017)
We provide a synopsis to the family Hymenophyllaceae in Bolivia, comprising 7 genera and 75 species, 2 of which are endemic to the country. One new species, Hymenophyllum (Sphaerocionium) jimenezii A.R.Sm. & M.Kessler, is described from Bolivia; additionally two new combinations are made: Didymoglossum punctatum subsp. sphenoides (Kunze) A.R.Sm. & M.Kessler and Polyphlebium herzogii (Rosenst.) A.R.Sm. & M.Kessler.